Pendidikan Seks pada Anak Usia Dini - Moh. Roqib (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Today, we have to be more alert because media and technology tend to facilitate free sex behavior, that more sophisticate and easy to access. One example is via cellular phone, with parent and government more permissive to it. Giving sex education early is because human basic character forming is at children age. Psychoanalyst shows that early years of children growth giving effect to children basic character growth. Wrong education can affect and became cause of sexual deviation on their next phase of life. Early age sex education can became mean of undeviating sexual apprehension and act, positively.